EDNA metabarcoding reveals a core and secondary diets of the greater horseshoe bat with strong spatio‐temporal plasticity. Issue 1 (4th December 2020) - Tournayre, Orianne; Leuchtmann, Maxime; Galan, Maxime; Trillat, Marine; Piry, Sylvain; Pinaud, David; Filippi‐Codaccioni, Ondine; Pontier, Dominique; Charbonnel, Nathalie
Abstract: Dietary plasticity can be a determining factor allowing species to cope with environmental changes. Consequently, it is an important issue to consider in conservation biology. Despite this, it remains rarely addressed in the literature, potentially due to methodologies which were until recently rather limited. The advent of molecular approaches now makes it possible to get a precise picture of diet and its plasticity, even for endangered and elusive species. Here, we focused on the greater horseshoe bat ( Rhinolophus ferrumequinum ) in Western France, where this insectivorous species has been classified as "Vulnerable" on the Regional Red List in 2016. We applied an eDNA metabarcoding approach to 1986 fecal samples collected in six maternity colonies on three sampling dates. We described the diet and investigated whether the landscape surrounding colonies and the different phases of the maternity cycle influenced the diversity and the composition of this diet. We showed that R. ferrumequinum feed on a much more diverse prey spectrum than expected from previous studies, highlighting how eDNA metabarcoding can improve our knowledge on the dietary habits of elusive species. Our approach also revealed that the diet of R. ferrumequinum seems to be composed of two distinct features: the core diet consisting of a few preferred taxa shared by all the colonies (25% of the occurrences) and the secondary diet consisting of numerous rare prey taxa that were highly different between colonies and sampling dates (75% of the occurrences). Constraints associated with the greater horseshoe bat life cycle, as well as insect phenology and landscape features, strongly influenced the diversity and composition of both the core diet and the diet as a whole. Further research should now explore the relationships between R. ferrumequinum dietary plasticity and fitness, to better assess the impact of core prey decline on R. ferrumequinum population viability. Abstract : Here, we focused on the greater horseshoe bat ( Rhinolophus ferrumequinum ) in Western France, where this insectivorous species has been classified as "Vulnerable" on the Regional Red List in 2016. We applied an eDNA metabarcoding approach to 1986 fecal samples collected in six maternity colonies on three sampling dates. We revealed that the diet of R. ferrumequinum seems to be composed of two distinct features: the core diet consisting in a few preferred taxa shared by all the colonies (25% of the occurrences) and the secondary diet consisting of numerous rare prey taxa that were highly different between colonies and sampling dates (75% of the occurrences). Constraints associated with the greater horseshoe bat life cycle, as well as insect phenology and landscape features, strongly influenced the diversity and composition of both the core diet and the diet as a whole.